Design of Hybrid-Electric Small Air Transports. Issue 1 (1st February 2022) - Orefice, F.; Marciello, V.; Nicolosi, F.; Zhang, Q.; Wortmann, G.; Menu, J.; Cusati, V.
Abstract: The potential benefits of hybrid-electric or full-electric propulsion have led to the proliferation of many concepts over the past decade. The lack of conceptual design methods capable of grasping the effects of the new propulsive technologies is often due to the absence of industrial data supporting the research. In the present work, two objectives are pursued. On the one hand, the introduction of semi-empirical methods for weight estimation based on the data provided by the industrial partners of the ELICA CS2 project. On the other hand, the establishment of generative engineering as a conceptual design tool for propulsive system architecting and fault tolerance analysis. The applications of the proposed conceptual design methods deal with two different years of entrance in service.